1984
DOI: 10.1111/j.1600-0528.1984.tb01434.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental defects of enamel in a group of New Zealand children: their prevalence and some associated etiological factors

Abstract: The prevalence of developmental defects of enamel was assessed in 243 children aged 12-14 yr using the FDI Index. The teeth were not cleaned or dried prior to examination for which fibre optic lighting was used. At least one tooth with defective enamel was seen in 63% of children with a demarcated white opacity present in 44% of children. The enamel was abnormal in 11.7% of teeth, diffuse patchy opacities and demarcated white opacities occurring in 4.4 and 4.2%, respectively. Although defects were found most f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
3
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 19 publications
7
51
3
2
Order By: Relevance
“…The present study supports previous fi ndings that the prevalence of DDE is associated with the fl uoride concentration of the available drinking water, and that the occurrence of diffuse opacities can be a discriminating factor between the high-fl uoride and low-fl uoride groups [Suckling and Pearce, 1984;Cutress et al, 1985;Clarkson and O'Mullane, 1989;de Liefde and Herbison, 1989;Angelillo et al, 1990;Milsom and Mitropoulos ,1990;Nunn et al, 1993;Ekanayake and van der Hoek, 2003]. However, the mouth prevalence fi gures of 89.3% in 1983 ([F] 1.0 ppm), 48.5% in 1991 ([F] 0.7 ppm), and 32.4% in 2001 ([F] 0.5 ppm) for diffuse opacities in the current study ( table 1 ) are higher than that reported in other studies with similar concentrations of fl uoride in the public water [Cutress et al, 1985;de Liefde and Herbison, 1985;Angelillo et al, 1990;Milsom and Mitropoulos, 1990;Holt et al, 1994;Dini et al, 2000].…”
Section: Discussionsupporting
confidence: 79%
“…The present study supports previous fi ndings that the prevalence of DDE is associated with the fl uoride concentration of the available drinking water, and that the occurrence of diffuse opacities can be a discriminating factor between the high-fl uoride and low-fl uoride groups [Suckling and Pearce, 1984;Cutress et al, 1985;Clarkson and O'Mullane, 1989;de Liefde and Herbison, 1989;Angelillo et al, 1990;Milsom and Mitropoulos ,1990;Nunn et al, 1993;Ekanayake and van der Hoek, 2003]. However, the mouth prevalence fi gures of 89.3% in 1983 ([F] 1.0 ppm), 48.5% in 1991 ([F] 0.7 ppm), and 32.4% in 2001 ([F] 0.5 ppm) for diffuse opacities in the current study ( table 1 ) are higher than that reported in other studies with similar concentrations of fl uoride in the public water [Cutress et al, 1985;de Liefde and Herbison, 1985;Angelillo et al, 1990;Milsom and Mitropoulos, 1990;Holt et al, 1994;Dini et al, 2000].…”
Section: Discussionsupporting
confidence: 79%
“…Data presented in figures 1 and 2 indicating that maxil lary incisor teeth are the most affected teeth are in agree ment with other surveys [Murray and Shaw, 1979;Suckling andPearce, 1984: Dummer et al, 1986;Angelillo et al, 1990]. However, Nunn et al [1993a] reported that in chil dren living in areas of Sri Lanka receiving above optimum fluoride levels in water, maxillary canine first premolar Caries Res 1997:31:259-267 teeth were affected more than maxillary incisor teeth, sug gesting that excessive fluoride ingestion occured at a later age in these Sri Lankan children.…”
Section: Discussionsupporting
confidence: 75%
“…This can be compared with 63 per cent of 12-14-year-old New Zealand children with at least one tooth with enamel defect when all the teeth were assessed. 15 These authors found the highest prevalence for demarcated opacities was among the maxillary first permanent molars (14 per cent) while the prevalence was 9 per cent on mandibular first permanent molars. They also found that the diffuse opacities were symmetrically distributed whereas the demarcated opacities were less likely to be symmetrical in their distribution.…”
Section: Discussionmentioning
confidence: 91%
“…[9][10][11][12] These studies varied in the criteria used to classify the enamel defects; the DDE index was used in the study by Zagdwon et al, 11 and in the study by Jasulaityte et al 12 a recently suggested case definition of MIH was used. Reports from New Zealand, using the DDE index, indicated a prevalence of 7-12 per cent 14 and 9-14 per cent 15 for the first permanent molars with demarcated opacities.…”
Section: Introductionmentioning
confidence: 99%